2005
DOI: 10.1097/01.mol.0000174153.53683.f2
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and the metabolic syndrome

Abstract: Nonalcoholic fatty liver disease prevalence in Western countries is high and there is a trend towards a further increase, with millions of people at risk of advanced liver disease. The epidemiological evidence, the lifestyle origin of the disease and the cost of pharmacotherapy make prevention a primary goal, and will contribute to making behavior therapy the background treatment. We need specific programs and carefully controlled, randomized studies to tackle simultaneously all the components of the metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
357
0
18

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(385 citation statements)
references
References 43 publications
10
357
0
18
Order By: Relevance
“…This finding provides further evidence that ALT and other serum liver enzymes appear to be insensitive markers for NAFLD, especially in the type 2 diabetic population. Indeed, it is well known that the full histological spectrum of NAFLD may be present among patients with 'normal' serum liver enzymes, which therefore cannot be reliably used to exclude the presence of advanced NAFLD [1][2][3][4]. Our finding further supports the notion that the 'normal' reference values for serum liver enzymes currently used to exclude NAFLD need to be revised [2,21,22].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This finding provides further evidence that ALT and other serum liver enzymes appear to be insensitive markers for NAFLD, especially in the type 2 diabetic population. Indeed, it is well known that the full histological spectrum of NAFLD may be present among patients with 'normal' serum liver enzymes, which therefore cannot be reliably used to exclude the presence of advanced NAFLD [1][2][3][4]. Our finding further supports the notion that the 'normal' reference values for serum liver enzymes currently used to exclude NAFLD need to be revised [2,21,22].…”
Section: Discussionsupporting
confidence: 68%
“…Non-alcoholic fatty liver disease (NAFLD), in its whole spectrum of disease ranging from simple steatosis to steatohepatitis and cirrhosis, is the most common cause of abnormal liver function tests among adults in Western countries [1][2][3][4]. The prevalence of NAFLD has been reported to be in the 15 to 30% range in the general population in various countries [5][6][7] and is almost certainly increasing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity can reduce muscle insulin resistance [20,21]; however, studies have also shown that physical activity is associated with a lower intrahepatic fat content [22], and that intrahepatic fat content is associated with hepatic insulin sensitivity [23,24]. Consequently, a differential effect of physical activity on progression to diabetes in individuals with i-IFG and i-IGT could be expected.…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD predicts development of the metabolic syndrome and is involved in the pathophysiology of atherosclerosis, insulin resistance and type 2 diabetes [1][2][3][4][5][6][7]. While these data emphasise the critical role of fatty liver in human metabolism, the mechanisms involved in the process of hepatic fat accumulation in humans are not fully understood.…”
Section: Introductionmentioning
confidence: 99%